INTEGRASI EPISTEMOLOGI ISLAM DALAM MANAJEMEN KURIKULUM: STUDI KARAKTERISTIK FILSAFAT ILMU DI PESANTREN RAUDHATUT THOLABAH SETAIL BANYUWANGI - Mohamad Hisyam Syafa’at; Muhammad Hadi Lukman (Hijri, 2025)
Contemporary Islamic education faces the challenge of a dichotomy between classical scholarly traditions (naqliyah) and modern science (aqliyah). This study aims to analyse curriculum management at Pesantren Raudhatut Tholabah Setail, which uniquely integrates the study of classical Islamic texts (kitab kuning) by Imam al-Ghazali, formal education, and students' economic self-reliance practices. The research employs a qualitative approach with a case study design to understand curriculum management at Pesantren Raudhatut Tholabah Setail, particularly the integration of Islamic epistemology (Bayani, Burhani, Amali) with formal education and students' economic activities. Data were collected through participatory observation, documentation, and semi-structured interviews with the caregivers (pengasuh), teachers, and students. The data were analysed thematically to identify patterns, themes, and categories, with validity maintained through source triangulation and member checking. This method enables an in-depth understanding of holistic educational practices that unify theory, practice, and moral values. The study shows that curriculum management at Pesantren Raudhatut Tholabah Setail successfully integrates the three dimensions of Islamic epistemology-Bayani (classical texts), Burhani (reason), and Amali (practice)-within a holistic educational system. Students' economic activities, such as selling getuk, function as a phronesis laboratory for transforming theoretical knowledge into real-life experience, fostering independence, discipline, and moral values. The integration of formal education and classical scholarly traditions enables balanced academic and spiritual development. The roles of teachers and caregivers as facilitators and adaptive leaders are crucial in ensuring the harmonisation of all curriculum components. This model produces graduates who are intellectually capable, spiritually mature, and equipped with adaptive life skills, making education relevant, holistic, and character-oriented